2019
DOI: 10.1016/j.aott.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical trends in zone 2 flexor tendon repair between Turkish and international surgeons

Abstract: The role of the platelet-to-lymphocyte ratio and neutrophil-to-lymphocyte ratio in the prediction of length and cost of hospital stay in patients with infected diabetic foot ulcers: A retrospective comparative study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Despite the efforts of several authors, no universally accepted treatment for flexor tendon injuries has evolved. Tendon surgery is to provide tendon healing with adequate tensile strength, adhesion reduction, proper tendon gliding and excursion [22]. Our Patients were treated with primary repair utilizing the 4-strand approach in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the efforts of several authors, no universally accepted treatment for flexor tendon injuries has evolved. Tendon surgery is to provide tendon healing with adequate tensile strength, adhesion reduction, proper tendon gliding and excursion [22]. Our Patients were treated with primary repair utilizing the 4-strand approach in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Different sutures have been studied, in vitro as well as in vivo, with different numbers of strands and knots, with the aim of achieving the greatest resistance while promoting the sliding of the tendon in its sheath, during mobilization, throughout the tendon healing period, which is estimated at 12 weeks on average [8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have emerged comparing two-strand and four-strand sutures over the past few years in patients with wounds in different areas or on multiple fingers [8][9][10][11][12]16]. These studies demonstrated the superiority of more than two strands, which would promote early mobilization with less risk of rupture during the critical period of tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons are wary about delay primary repair (Unsal et al, 2019), although it is possible and used commonly (Reito et al, 2019). Unsal et al (2019) sent a questionnaire about flexor tendon repair, and received 91 responses from international surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons are wary about delay primary repair (Unsal et al, 2019), although it is possible and used commonly (Reito et al, 2019). Unsal et al (2019) sent a questionnaire about flexor tendon repair, and received 91 responses from international surgeons. Thirty-four per cent of respondents considered 3 weeks to be the maximum limit for primary repair, 32% considered the limit to be 4 weeks and 36% consider the limit to be 5 weeks.…”
Section: Discussionmentioning
confidence: 99%